Leucine‐Rich Glioma‐Inactivated 1 versus Contactin‐Associated Protein‐like 2 Antibody Neuropathic Pain: Clinical and Biological Comparisons. Issue 4 (30th August 2021) - Ramanathan, Sudarshini; Tseng, Mandy; Davies, Alexander J.; Uy, Christopher E.; Paneva, Sofija; Mgbachi, Victor C.; Michael, Sophia; Varley, James A.; Binks, Sophie; Themistocleous, Andreas C.; Fehmi, Janev; Anziska, Yaacov; et al.
Abstract : Pain is a under‐recognized association of leucine‐rich glioma‐inactivated 1 (LGI1) and contactin‐associated protein‐like 2 (CASPR2) antibodies. Of 147 patients with these autoantibodies, pain was experienced by 17 of 33 (52%) with CASPR2‐ versus 20 of 108 (19%) with LGI1 antibodies ( p  = 0.0005), and identified as neuropathic in 89% versus 58% of these, respectively. Typically, in both cohorts, normal nerve conduction studies and reduced intraepidermal nerve fiber densities were observed in the sampled patient subsets. In LGI1 antibody patients, pain responded to immunotherapy ( p  = 0.008), often rapidly, with greater residual patient‐rated impairment observed in CASPR2 antibody patients ( p  = 0.019). Serum CASPR2 antibodies, but not LGI1 antibodies, bound in vitro to unmyelinated human sensory neurons and rodent dorsal root ganglia, suggesting pathophysiological differences that may underlie our clinical observations. ANN NEUROL 2021;90:683–690